2012
DOI: 10.1016/j.reprotox.2012.04.003
|View full text |Cite
|
Sign up to set email alerts
|

No effects of MRI scan on male reproduction hormones

Abstract: This is an accepted version of a paper published in Reproductive Toxicology. This paper has been peer-reviewed but does not include the final publisher proof-corrections or journal pagination.Citation for the published paper: Møllerløkken, O., Moen, B., Baste, V., Magerøy, N., Oftedal, G. et al. (2012) "No effects of MRI scan on male reproduction hormones." Reproductive Toxicology URL: http://dx.doi.org/10. 1016/j.reprotox.2012.04.003 Access to the published version may require subscription. A prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The effects on male reproductive hormones were investigated in 24 healthy, male volunteers exposed to 1.5 T MRI. No differences were observed in the serum blood level of a series of key hormones neither immediately after, nor after 11 days of MRI and sham exposure [103].…”
Section: Effects Of Multiple Exposures 13mentioning
confidence: 79%
“…The effects on male reproductive hormones were investigated in 24 healthy, male volunteers exposed to 1.5 T MRI. No differences were observed in the serum blood level of a series of key hormones neither immediately after, nor after 11 days of MRI and sham exposure [103].…”
Section: Effects Of Multiple Exposures 13mentioning
confidence: 79%
“…As it was stated earlier, the numerous studies conducted on humans and animals regarding the effects of EMFs on reproductive indices have controversial and contradictory reports ( Wang et al, 2016 ). Certain studies on humans report that exposure to EMFs does not cause any changes to male reproductive indices ( Hjollund et al, 1998 ; Møllerløkken et al, 2012 ). Many animal studies report that exposure to EMFs can cause reductions in reproductive indices such as testosterone ( Kesari & Behari, 2012 ; Sepehrimanesh et al, 2014 ; Shahin et al, 2014 ) but can in some cases increase testosterone ( Forgács et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…20 The results of human and animal studies have differed on the effects of EMF radiation on reproductive hormones. 21 While a number of human and animal studies have reported no change in male reproductive hormones at exposure to EMF, 11,[22][23][24][25][26][27][28][29][30] others have claimed that exposure to EMF can decrease testosterone levels. 18,20,[31][32][33][34][35] Even in some cases, increases in testosterone, LH, and FSH have been reported.…”
Section: Introductionmentioning
confidence: 99%